Stone tools : theoretical insights into human prehistory - Odell, George H. (Interdisciplinary contributions to archaeology., 1996)
Lithic analysts have been criticized for being atheoretical in their approach, or at least for not contributing to building archaeological theory. This volume redresses that balance. In Stone Tools, renowned lithic analysts employ explicitly theoretical constructs to explore the archaeological record and use the lithic database to establish its points. Chapters discuss curation, design theory, replacement of stone with metal, piece refitting, and projectile point style.